Green wealth : navigating towards a sustainable future - Grima, Simon; Maditinos, Dimitrios; Noja, Grațiela-Georgiana; Stankevičienė, Jelena; Tarczynska-Luniewska, Malgorzata; Thalassinos, Eleftherios I.; Nermend, Kesra (Emerald Publishing Limited, 2025)
Today, economic growth must be in harmony with environmental sustainability. Green Wealth: Navigating towards a Sustainable Future delves into the connection between financial prosperity and ecological accountability, addressing several aspects of sustainable development, such as renewable energy, circular economy, green technology, sustainable agriculture, and conservation initiatives. Green Wealth examines the financial advantages of implementing sustainable practices in different industries. Through examination of case studies of firms, expert interviews, literature research and data analysis, important lessons are learned, and actions are recommended. This book aims to contribute to the worldwide discussion on sustainable development and encourage positive change through well-defined goals, a wide range of topics, thorough methodology, and practical outcomes. Contemporary Studies in Economic and Financial Analysis publishes a series of current and relevant themed volumes within the fields of economics and finance. Both disciplinary and interdisciplinary studies are welcome.
Includes index.
Keywords: Sustainable development.; Economic development.; Business & Economics -- Development -- Sustainable Development.; Environmental economics.; Development economics and emerging economies.; Sustainability.; elektronické knihy; electronic books